Volume Navigation Technique for Ultrasound-Guided Biopsy of Breast Lesions Detected Only at MRI - (:unkn) unknown (AMER ROENTGEN RAY SOC, 2017)
OBJECTIVE. The purpose of this study is to assess the utility of a volume navigation technique (VNT) for ultrasound-guided biopsy of MRI-detected, but sonographically ambiguous or occult, breast lesions. SUBJECTS AND METHODS. Within a recruitment period of 13 months (January 1, 2014, through February 1, 2015), 22 patients with 26 BI-RADS category 4 or 5 lesions that were detected at MRI but missed at second-look ultrasound were reimaged using a rapid sequence and a flexible body coil in a 3-T MRI scanner. Patients were supine, with three skin markers placed on the breasts. MRI volume data were coregistered to real-time ultrasound in a dedicated platform, and MRI-detected lesions (six masses, 11 nonmass enhancements, eight foci, and one architectural distortion) were sought using VNT-guided ultrasound. Five needle biopsy specimens were obtained either from each sonographically detected lesion (n = 11) or from VNT-guided sonographically localized breast volume corresponding to the MRI-detected, but still ultrasound-occult, lesions (n = 15). RESULTS. Histopathologic analysis revealed 18 benign and six malignant lesions. The remaining two lesions, both of which appeared as masses at MRI, were high risk and were upgraded to carcinoma after excisional biopsy. All malignant lesions underwent curative surgery; the final histopathologic diagnoses remained unchanged. Of the six malignant lesions, one was a mass, three were nonmass enhancements, and two were enhancing foci at MRI. Three malignant lesions were occult at ultrasound, and three were discerned as subtle hypoechoic changes. No benign lesion was sonographically visualized as a mass, and none progressed, with 56% disappearing at MRI performed during the follow-up period (mean, 14 months). CONCLUSION. Coregistration of MRI and real-time ultrasound enables sonographic localization of breast lesions detected at MRI only. VNT is a feasible alternative to MRI-guided biopsy of ultrasound-occult breast lesions.
Keywords: breast lesion; breast ultrasound; MRI; ultrasound-guided biopsy; volume navigation technique; TARGETED ULTRASOUND; IDENTIFICATION; FEASIBILITY; SONOGRAPHY; DIAGNOSIS; ACCURACY; UTILITY; SYSTEM; CANCER; WOMEN